Stress from an administrative perspective in public transport drivers in Mexico City: Minibus and metrobus (Estudios Gerenciales, 2016)
Stress is one of the occupational diseases that affect workers worldwide, affecting their own productivity and performance (as well as that of the organizations where they work), and even their physical and mental health. According to the International Labour Organization, Mexican workers suffer from stress the most all over the world, since theirs is one of the most stressful professions. With this in mind, the aim of this research is to study the work stress in bus rapid transit drivers and minibus in Mexico City. The method used is based on an exploratory statistical factorial analysis. It is concluded that the factors which a higher influence in the onset of stress are organizational, environmental (physical/individual), inherent to the position, extra organizational and individual. Although divergent among drivers, minibus drivers are the workers who suffer the most from stress.